Therapeutic Management of the Posttraumatic Stiff Elbow After Open Osteocapsular Release. Issue 4 (December 2018) - Cancio, Jill M.; Rhee, Peter
Abstract : Arthrofibrosis is an inevitable consequence of elbow trauma that oftentimes requires surgical release to restore range of motion and function. Although the surgical procedure for elbow osteocapsular release can result in marked improvement in elbow motion, postrelease rehabilitation is paramount to maintaining and even improving the gains achieved in surgery. There are a variety of rehabilitation protocols and modalities that can be implemented that can be divided into an early versus late stage of rehabilitation after surgery. Irrespectively, patient ownership in the rehabilitative process and effective communication between surgeon and therapist are integral in achieving successful outcomes. Abstract : Supplemental Digital Content is available in the text.